2014
DOI: 10.5455/2320-6012.ijrms20140242
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study on the prevalence of reproductive tract infections amongst married women in the rural area of Surendranagar district

Abstract: pregnancy, abortion, child bearing and contraception. High levels of gynaecological morbidity, especially reproductive tract infections and sexually transmitted infections may turn out to be fatal if not treated properly. 3 Aims and objectivesTo find out the prevalence of reproductive tract infections amongst married women in the rural areas of Surendranagar district and to co-relate the disease with certain socio demographic variables, to find out the basic ABSTRACT Background: In the recent years, the issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
2
9
1
Order By: Relevance
“…Prevalence reported in our study is lower than that reported by Thekdi KP, et al 11 (56.5%), but much higher than that reported in other studies. 12,13,14 The prevalence of RTI was significantly associated with age, being maximum in 25-29 years (63.7%) followed by 36.5% in 15-19 years.…”
Section: Discussioncontrasting
confidence: 56%
“…Prevalence reported in our study is lower than that reported by Thekdi KP, et al 11 (56.5%), but much higher than that reported in other studies. 12,13,14 The prevalence of RTI was significantly associated with age, being maximum in 25-29 years (63.7%) followed by 36.5% in 15-19 years.…”
Section: Discussioncontrasting
confidence: 56%
“…10 Another study showing the prevalence of reproductive tract infections among recently married women in Veerapandi Panchayat Union of Salem District, Tamil Nadu done by Kannan et al, showed the prevalence of RTIs to be 44.6%. 8 A study done among rural women in Meerut by Jain et al, found the prevalence of RTIs to be 44.8%. 12 All these studies were almost in accordance with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common symptom was lower abdominal pain, 63.9% suffered from it whereas the least reported symptom was burning pain during micturition (1.4%) vaginal discharge was also the commonest symptom reported in other studies in rural areas of India. [7][8][9][13][14][15][16]22 Among the other symptoms low back pain was the commonest symptom in a study conducted in Goa and dysuria was reported to be commonest in a study conducted in Ludhiana. 11,19 In the present study, none of them complained of genital ulcers and genital warts.…”
Section: Discussionmentioning
confidence: 99%
“…3 The study carried out by Thekdi et al, 56.5% of women reported either one or more symptoms of reproductive tract infections. 4 A study conducted in rural Haryana in which prevalence of reproductive tract infection was 61%. 5 A study conducted in highlands and coastal region of Peru where 77% of women reported symptoms of reproductive tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by Thekdi vaginal discharge was the most common symptom reported by (26.3%) followed by vulval itching (8.8%), low backache (7.0%), burning micturition (3.3%). 4 A study conducted in West Bengal in which 21.8% of women reported vaginal discharge as the commonest symptom followed by vulval itching (17.7%). 8 A study conducted by Chellan et al, in South India in which the vaginal discharge was the commonest symptom (32.2% Regarding prevalence of reproductive tract infections and literacy, maximum prevalence was found among women with education up to primary class (71.01%) who gradually decreased as the education of women increased.…”
Section: Discussionmentioning
confidence: 99%